Nucleotide Diversity at Site 106 of EPSPS in Lolium perenne L. ssp. multiflorum from California Indicates Multiple Evolutionary Origins of Herbicide Resistance - Karn, Elizabeth; Jasieniuk, Marie (Frontiers in Plant Science, 2017)
The repeated evolution of herbicide resistance in weeds is an ongoing problem in agricultural regions across the world, and presents a unique system in which to study the origins and spread of adaptive traits across heterogeneous landscapes. Lolium perenne ssp. multiflorum (Lam.) (Italian ryegrass) is a widespread grass weed of agricultural crops that has repeatedly evolved resistance to herbicides across the world. In California, resistance to glyphosate has become increasingly common. To identify the mechanisms conferring glyphosate resistance in California populations of L. perenne and to gain insights into the evolutionary origins and spread of resistance in the region, we investigated the frequency of target-site mutations conferring resistance to glyphosate combined with the frequency of resistant individuals in 14 populations. A region of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) was sequenced in 401 individuals to assay for target site mutations. Seven unique alleles were detected at codon site 106, four of which have been previously shown to confer target-site-based resistance to glyphosate. Four different resistance alleles were detected, indicating that resistance to glyphosate has evolved multiple times in the region. In two populations, no EPSPS mutations were detected despite the presence of resistant plants, strongly suggesting that non-target-site-based mechanisms confer resistance to glyphosate in these populations. It is likely that resistance to glyphosate in these 14 California populations of L. perenne derives from at least five evolutionary origins, indicating that adaptive traits can evolve repeatedly over agricultural landscapes.